Wave model for coastal structures - Gregorio, Enrico G. (Philippine Engineering Journal)
Wave models as a planning and design tool are used to predict the influence of environmental conditions on a proposed harbour layout. These models have to satisfy similarity criteria as described herein. Factors such as wave climate, scale selection, hydrographic surveys, instrumentation and documentation influencing the design of the wave models are discussed. The use of wave disturbance test and stability test in arriving at the optimum port layout and breakwater cross-section, respectively is also explained.